Effect of tiopronin on excretion of homocysteine and its plasma exposure level in rats. Issue 3 (June 2016) - Miyajima, Atsushi; Bamba, Masaru; Onohara, Takeshi; Hirota, Takashi
Abstract: When the biosynthesis of homocysteine (Hcy), an amino acid containing thiol, exceeds its elimination, plasma Hcy concentration increases and results in hyperhomocysteinemia (HHC). Most of the Hcy in plasma covalently binds to the cysteine residues of albumin by disulfide bonds. Meanwhile tiopronin (TP), a thiol-containing compound, is used for treatment of cysteinuria to decrease the amount of insoluble cystine in urine, by replacing a cysteine molecule in cystine with TP to form soluble TP-cysteine complexes. The present study investigated the effect of TP on the total (protein-unbound and protein-bound) Hcy concentration and the ratio of protein-unbound Hcy to total Hcy in plasma, and the urinary excretion of Hcy. Methionine was administered orally to rats to induce temporary hyperhomocysteinemia, and then TP was administered and the plasma and urine were collected. The amount of Hcy excreted in urine was higher but the plasma concentration of Hcy was lower in the TP group than in the control group until 3 h after TP administration. In addition the ratio of protein-unbound Hcy in plasma tended to be increased by TP administration. These results demonstrated that TP enhanced the urinary excretion of Hcy, which might cause the decrease of its plasma concentration in rats.